2008
DOI: 10.3168/jds.2007-0721
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Limited Methionine Diets with Rumen-Protected Methionine, Betaine, and Choline in Early Lactation Holstein Cows

Abstract: Eighty lactating Holstein cows from 21 to 91 d in milk were fed a corn silage-based total mixed ration (TMR) formulated with the Met content limited (42 g/ d) to investigate the impact of supplementing rumen-protected (RP) forms of Met, betaine, and choline on performance and metabolism. One of 4 supplements was blended into the TMR to produce 4 dietary treatments: 1) control, 2) 20 g/d of RP-Met, 3) 45 g/d of RP-betaine, and 4) 40 g/d of RP-choline. Calcium salts of fatty acids were used to protect both RP-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
102
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 23 publications
19
102
4
2
Order By: Relevance
“…On the other hand, At their recent study, Phillips et al 25 demonstrate that inclusion of methionine into diets of cows drops off their serum TG at postpartum 1 st week. By contrast, the studies using methionine during early lactation period report no change in serum TG levels 26,27 . Xu et al 28 discloses that the addition of rumen-protected amino acids containing methionine (13 g/day) and lysine (40 g/day) into the rations of multiparous Holstein dairy cattle reduces serum levels of TG and NEFA.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…On the other hand, At their recent study, Phillips et al 25 demonstrate that inclusion of methionine into diets of cows drops off their serum TG at postpartum 1 st week. By contrast, the studies using methionine during early lactation period report no change in serum TG levels 26,27 . Xu et al 28 discloses that the addition of rumen-protected amino acids containing methionine (13 g/day) and lysine (40 g/day) into the rations of multiparous Holstein dairy cattle reduces serum levels of TG and NEFA.…”
Section: Discussionmentioning
confidence: 80%
“…This condition can be associated with increased VLDL catabolism in mammary glands and excessive fat accumulation in liver 2 . Davidson et al 26 added methionine to diets of cows at their early lactation period but observed no change in their VLDL concentrations. In the current study at evaluations within the groups, we measured numerically the lowest VLDL concentration in control and methionine groups at postpartum 2 w but at postpartum 2 w in Group L and Group LM.…”
mentioning
confidence: 99%
See 3 more Smart Citations